Pelatihan Cara “Transactions dan Promotions” Menggunakan Bahasa Inggris Bagi UMKM di Desa Sumber Arum Kabupaten Seluma - Gustini, Gustini; Hamid, Anwar; Putri, Sudriyanti; Farozi, Nour; Dwisnu, Erlian (Jurnal Semarak Mengabdi, 2022)
The purpose of this activity is to provide training to UMKM actors in Sumber Arum Village, Seluma Regency, who are considered less able to present and promote their products to consumers mainly from the country. in addition to English and limited English communication skills, including: English vocabulary level, English pronunciation ability is still weak, English grammar ability both spoken and written are weak. Therefore, the dedication of STIA Bengkulu instructors to carry out activities can enhance the capacity of UMKM, especially in conducting transactions and promoting in English. From these activities, MSME members find it very useful and start trying to apply what they have learned in training activities.